BACTERIOLOGICAL PROFILE OF WOUND INFECTION AND ANTIBIOTIC SUSCEPTIBILITY PATTERNS IN A PUBLIC HOSPITAL IN SURABAYA, INDONESIA - Ayunur Kholifah, Ika; Wahyu Indriati, Dwi; Wahyuni , Ratna; Sundari, Aliyah Siti (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Pyogenic infections that occur can be caused by direct bacterial contamination of the wound, such as infection in a post-surgical wound or infection after trauma. Efforts to control infection can be done with the use of antibiotics. Purpose: To determine the profile of bacteria and antibiotic sensitivity in wound culture in hospitalized patients in Hajj General Hospital Surabaya, East Java in 2021. Method: This study used the Chi-square test and descriptive analysis in the form of distribution tables and percentages using secondary data based on the results of examination of pus culture at the Clinical Microbiology Laboratory in Hajj General Hospital Surabaya, East Java in 2021. Result: The results of research on wound culture samples showed as many as 113 patients (56.22%) with positive culture results, which were predominantly female as many as 59 patients (50.9%) and the highest age category namely at the age of 46-55 years as many as 39 patients (33.6%). Based on bacteria, the most dominant type of bacteria in the Gram-negative group was Escherichia coli ESBL with 21 isolates (26.6%), while Gram-positive bacteria, Staphylococcus aureus, was found in 16 isolates (43.3). The results of antibiotic sensitivity on Gram-negative bacteria were Piperacillin/Tazobactam and Meropenem, and on Gram-positive bacteria Vancomycin and Linezolid were obtained. Conclusion: E. coli and S. aureus are the most important causes of wound infections and the suppressor organisms in this study. Antibiotic susceptibility testing of all isolates showed that the antibiotics amikacin and meropenem were sensitive to Gram-negative bacteria especially ESBL-producing bacteria, and the antibiotics vancomycin and linezolid were sensitive to Gram-positive bacteria especially MRSA.